2014
DOI: 10.5664/jcsm.4284
|View full text |Cite
|
Sign up to set email alerts
|

Does Neck-to-Waist Ratio Predict Obstructive Sleep Apnea in Children?

Abstract: Objectives: Central adiposity and large neck circumference are associated with obstructive sleep apnea (OSA) in adults but have not been evaluated in children as predictors of OSA. Study objectives were to determine whether (1) anthropometric measures including neck-to-waist ratio are associated with OSA in older children; (2) body fat distribution, measured by neck-to-waist ratio, is predictive of OSA in overweight/obese children. Methods: Cross-sectional study involving children 7-18 years scheduled to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 37 publications
5
24
2
1
Order By: Relevance
“…Our study observed that obesity, defined as BMI above the 95 th percentile, was significantly related to OSAS in children. Meanwhile, Katz et al reported that neck to waist ratio, an index of body fat distribution, predicts OSA in older children and youth who are obese or overweight [33]. Similarly, we found neck circumference ≥ 30 cm, neck/height ratio ≥ 0.25 and waist/hip ratio ≥ 0.95 were associated with OSA.…”
Section: Discussionsupporting
confidence: 77%
“…Our study observed that obesity, defined as BMI above the 95 th percentile, was significantly related to OSAS in children. Meanwhile, Katz et al reported that neck to waist ratio, an index of body fat distribution, predicts OSA in older children and youth who are obese or overweight [33]. Similarly, we found neck circumference ≥ 30 cm, neck/height ratio ≥ 0.25 and waist/hip ratio ≥ 0.95 were associated with OSA.…”
Section: Discussionsupporting
confidence: 77%
“…Katz et al reported on 222 children between the ages of 7 and 18 years who were referred to primary care physicians for SDB; 60% had overweight or obesity. They found the neck-to-waist ratio to be an independent predictor of OSA, except in children with a BMI greater than the 99th percentile (15). In our population, neither neck circumference nor waist circumference correlated with oAHI or oxygen saturation nadir; however, sagittal abdominal diameter was significantly correlated with both oAHI and the oxygen saturation nadir.…”
Section: Discussioncontrasting
confidence: 64%
“…15 Katz et al had shown that neck to waist ratio, an index of body fat distribution predicts obstructive sleep apnoea in overweight/obese children. 16 Another study conducted in 324 Greek children aged 9 -13 years found that NC was associated with most cardiovascular disease (CVD) risk factors. The study showed that the association of NC and CVD was comparable to the observed co-relations of BMI, WC, hip circumference (HC), waist-to-hip ratio (WHR) and WHtR with CVD.…”
Section: Discussionmentioning
confidence: 99%